Excess deaths associated with long-term exposure to ambient NO2 in China. (1st December 2022) - Qi, Ling; Fu, Anqi; Duan, Xiaoli
Abstract: World Health Organization updated the target of annual mean NO2 from 40 μ g m −3 to 10 μ g m −3 in 2021 based on new evidences that showed statistically independent effects of long-term exposure to ambient NO2 and mortality. We estimate the excess deaths associated with long-term exposure to ambient NO2 (DAAN) from non-accidental disease (NAD), cardiovascular disease (CVD) and respiratory disease (RD) in China in 2013–2020 using a counterfactual analytic framework adopted by Global Burden Disease. We use relative risk (RR) values based on a meta-analysis, and assume a linear concentration-response (C-R) function and a threshold value of 10 μ g m −3 . DAAN from NAD vary in 279 (95% Cl: 189–366) to 339 (95% Cl: 231–442) thousand in 2013–2020, comparable to excess deaths attributed to long-term exposure to ambient O3 in China. DAAN from NAD changes by −43%–+220% using different RR values, C-R function shapes, and threshold values. DAAN from RD reduces while those from CVD increases significantly in 2013–2020. DAAN from RD account for ∼10% of total DAAN. We found that the reduction of NO2 concentration and baseline mortality of NAD offsets the adverse effects of population growth and aging in 2013–2017. In 2017–2020, the contribution from air pollution reduction surpasses the adverse effects of population growth and aging in most regions. We suggest that continuing the reduction rate of NO2 emissions in 2013–2020 would offset the effects of population growth and aging in 2020–2030. Faster reduction of NO2 sources is required to reduce DAAN in Liaoning, Shanxi, Shanghai, and Anhui, where DAAN from NAD, CVD and RD increased in 2013–2020. Our results should be interpreted with caution because the causality support of long-term exposure to ambient NO2 on mortality from toxicological studies is not firm yet, and NO2 is possibly just a marker of traffic-related pollutants.